2014
DOI: 10.3390/s140406722
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Manufacturing of a Micromachined Magnetic Sensor Using the CMOS Process without Any Post-Process

Abstract: The modeling and fabrication of a magnetic microsensor based on a magneto-transistor were presented. The magnetic sensor is fabricated by the commercial 0.18 μm complementary metal oxide semiconductor (CMOS) process without any post-process. The finite element method (FEM) software Sentaurus TCAD is utilized to analyze the electrical properties and carriers motion path of the magneto-transistor. A readout circuit is used to amplify the voltage difference of the bases into the output voltage. Experiments show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 30 publications
0
19
1
Order By: Relevance
“…Leepattarapongpan et al [30] developed an MF microsensor with a 110 mV/T sensitivity. Tseng et al [10] made an MF microsensor whose sensitivity was 354 mV/T. The sensitivity of the MF microsensor in this work was higher than those of all three of these studies.…”
Section: Resultscontrasting
confidence: 39%
See 3 more Smart Citations
“…Leepattarapongpan et al [30] developed an MF microsensor with a 110 mV/T sensitivity. Tseng et al [10] made an MF microsensor whose sensitivity was 354 mV/T. The sensitivity of the MF microsensor in this work was higher than those of all three of these studies.…”
Section: Resultscontrasting
confidence: 39%
“…A standard 0.18 μm CMOS process of Taiwan Semiconductor Manufacturing Company (TSMC) was utilized to make the MF microsensor [10]. According to the MF microsensor model in Figure 1, we designed the layout of the MF microsensor.…”
Section: Fabrication Of Magnetic Field Sensormentioning
confidence: 99%
See 2 more Smart Citations
“…Fluxgate magnetometers are typically applied in craft navigation, military detection and medical recognition [3]. So far prospective applications of micro-fluxgates have been considerably developed for modern digital navigation , thoracoscopic surgery , and nondestructive inspection [4]. On device characterization of fluxgate magnetometers, several earlier works concluded that the sensing methodology and sensitivity enhancement by adopting the multiple harmonic frequency analysis techniques are practicable [5].…”
Section: Introductionmentioning
confidence: 99%